Przyczynek do dziejów Biblioteki Radzieckiej w Poznaniu - Artur Jazdon (Biblioteka)
The article recalls the events surrounding the issuing of the emergency appeal launched by the municipal authorities of the town of Poznań in 1874 for handing over books, journals and pamphlets to the Council Library. The aim behind the appeal was to collect as much material related to the history of the region and the contemporary issues of the areas that belong to the then Grand Duchy of Poznań as possible. On the basis of the analysis of the contents of the library Catalogue from the year 1883, i.e. the date when the effort was completed, one can say that, to a certain degree, the appeal led to a successful completion resulting in a quantitative development o f the resources. However, the author also points at the qualitative shortcomings in the ensuing growth of the collections. The employed analysis proves that the basic task of the appeal was not fulfilled and the library created in the process did not preserve sufficiently complete resource of works.